Penerapan Siklus Akuntansi untuk Meningkatkan Jumlah Usaha Mikro Kecil dan Menengah di Kota Pangkalpinang Provinsi Kepulauan Bangka Belitung - Nur Hidayati (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2015)
These days Small-Medium Enterprises (SME) have been run by people to improve economic income. Some kinds of SME business in Indonesia are services and commercials. However, because of the lack knowledge of accounting cycle, many enterprises cannot implement appropriate recording system according to general accounting recording. As the result, the SME owner cannot draw aside enterprise financial and personal financial. The case is that when the SME owners are planned on evolve their business, they can propose bank loan. But, there are conditions to propose bank loan, one of the conditions is appropriate financial report.The implementation of accounting cycle on SME can help the owner to manage their business that their business can be successful. It also can help to stimulate new SMEs especially in Pangkalpinang city.Key words –Accounting Cycle, SME